The role of personal models in clinical management: Exploring health care providers' beliefs about psoriasis. Issue 1 (30th July 2015) - Chisholm, Anna; Nelson, Pauline A.; Pearce, Christina J.; Keyworth, Chris; Griffiths, Christopher E. M.; Cordingley, Lis; Bundy, Christine; ,
Abstract : Objectives: Individuals' illness representations, including beliefs about psoriasis (a complex immune‐mediated condition), and their emotional responses to the condition guide self‐management behaviour. It is also plausible that health care providers' illness representations guide their own management of psoriasis. Patients commonly report poor health care experiences related to psoriasis, and the role of health care providers' beliefs, emotions, as well as their knowledge, experiences and behaviours ('personal models') in this is unexplored. This study aimed explore health care providers' personal models of psoriasis. Design and methods: Qualitative analysis of 23 semi‐structured interviews with health care professionals providing care for psoriasis patients was performed. Purposive sampling achieved maximum variation regarding participant discipline, level of experience, gender and age. The self‐regulatory/common sense model informed data collection and initial data analysis. Principles of framework analysis were used to generate predetermined and emergent key issues related to practitioners' personal models. Results: Three types of personal model emerged. Sophisticated–Linear Model: 70% of practitioners recognized psoriasis as a complex condition but managed it as a skin condition. Mixed Model: 17% of practitioners recognized/managed some elements of psoriasis as complex and some as a skin condition. Sophisticated–Sophisticated Model: 13% recognized and managed psoriasis as a complex condition. Across the data set, five themes emerged illustrating key patterns underpinning these different models including (1) Recognising complexity, (2) Putting skin first, (3) Taking on the complexities of psoriasis with the patient, (4) Aiming for clearance, and (5) Affective experiences within psoriasis consultations. Conclusions: Health care providers recognized psoriasis as a complex condition but commonly reported managing psoriasis as a simple skin condition. Providers' beliefs and management approaches varied in the extent to which they were consistent with one another; and their emotional experiences during consultations may vary depending upon their personal model. Findings could inform future dermatology training programmes by highlighting the role of health care providers' illness representations in clinical management of the condition. Statement of contribution What is already known on this subject? Health behaviour is predicted by underlying beliefs and emotions associated with an illness and its treatment. Few studies have examined health care providers' beliefs and emotions about the illnesses they manage in clinical practice. Many patients are dissatisfied with dermatology consultations and wish to be treated holistically. What does this study add? Qualitative exploration of health care providers' beliefs/emotions revealed their personal models of psoriasis. Providers' personal models of psoriasis vary in coherence and are often skin rather than whole person focused. Further investigation of health care providers' models of psoriasis and their impact on health outcomes is needed.